Effect of pruning intensity on performance of apple cultivars in environmentally friendly production systems - Dremák, P.; Gonda, I.; Holb, I. J. (International Journal of Horticultural Science, 2009)
The two worldwide accepted environmentally freindly production systems are integrated and organic. The two systems shows considerably differences in several practical production technology elements. These effects come forward in generative processes (e.g. flowering, fruit setting) and vegetative features (e.g. growth). The aim of our study was to study the effect of pruning intensity on growth features of cultivars in integrated and organic apple production. In early spring of 2009, we determined two pruning intensities (strong and week) on six scab resistant and tolerant cultivars. Strong pruning resulted in stronger shoot growth for all cultivars compared to weak pruning. It is obvious that pruning intensity had more effect on vegetative performance than conditional differences originates from integrated and organic production.